OECD, 식품경제에 관한 논의동향 - 강혜정 (한국농촌경제연구원, 2007)
2002년 이후 OECD에서 식품경제 논의는 활발히 이루어지고 있다. 주요 논의 내용은 소비자의 농식품 소비패턴의 변화와 정책과제, 식품공급체인 변화에 따른 농가수익 변화, 민간품질기준의 경제적 영향 등에 관한 것이다. 참고자료 ⑴ Standards and the shaping of the agro-food system: selected economic issues, AGR/CA/APM(2003.11), OECD. ⑵ Changing food lifestyles: Emerging consumer concerns, AGR/CA/APM(2004.10), OECD. ⑶ The long term outlook for changes in food consumption patterns: concerns and policy options, AGR/CA/APM(2004.10), OECD. ⑷ Private standards and the shaping of the agro-food system, AGR/CA/APM(2004.10), OECD. ⑸ Private standards and developing country access to the global supply chains, AGR/CA/APM(2005.11), OECD. ⑹ Interaction of public and private standards in the food chain, AGR/CA/APM(2005.11)(2006.10), OECD.